Improving Reading Comprehension of Grade Eight Students Throught Experience Text Relationship (ETR) Method - Megayanti Lasagena; R. Mertosono, Sudarkam; Maf'ulah, Maf'ulah; Darmawan, Darmawan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research aims to determine if the implementation of the Experience Text Relationship (ETR) method can improve the reading comprehension of grade eight students of SMP Negeri 14 Palu. The sample for this study consisted of the grade eight students Slamet Riyadi as the control group and grade eight students Pattimura as the experimental group, selected using cluster random sampling. The researcher used pencil and paper with a test method as the instrument for data collection in the pretest and posttest techniques. Based on the test results, the average pretest score in the control group was 64.1, while in the experimental group, it was 49.7. After treatment in the experimental group, there was an increase above the control group, as evidenced by an increase in the posttest. The posttest score in the control group was 77.13, while in the experimental group, it was 80.2. Furthermore, the researcher calculated the t-counted to be 5.625, applying a significance level of 0.05 with degrees of freedom (df) 58, and the t-table value was 1.684. This means that the t-value is greater than the t-table value, leading to the conclusion that the Experience Text Relationship method can improve students' reading comprehension more effectively.